La Gloire du peintre et les errements de l’Académie : des pistes pour l’étude des marines de Claude-Joseph Vernet au Salon - Gaudreau, Nicolas (RACAR : Revue d'art canadienne / Canadian Art Review, 2000)
Thomas Crow (1985) has established that the Academy’s Salon was the theatre of an art crisis in the France of Louis XV. This has inspired a comparison between the tempests and shipwrecks of Claude-Joseph Vernet (1714–1789) and his series Les Ports de France (1754–1765), commissioned on behalf of the King by Marigny. In the first part of the article, we examine the popularity of the former paintings. After analysing the enthusiastic response of Diderot in his Salons, directly inspired by Burke's treatise on the sublime, we show that the success of these paintings was in their power to produce strong emotions in the spectator’s mind. We then describe the perception of the sea in the eighteenth century in order to anchor Diderot’s critique in a body of non-artistic representations. The popularity of Vernet’s tempests and shipwrecks rests on a lack of social symbolism. This gives them a universal character with which, unlike the more aristocratie history painting, spectators of ail origins can identify. The last section deals with Les Ports de France. We begin by discussing the choice of landscape for such a prestigious work, which can be explained by the necessity to renew the image of the state. The choice of the seaport motif answered both the need of propaganda by imposing a unitary vision of France and the wish to recall Colbert’s heritage. Finally we analyse how the King and the Salon received the series by concluding that it was ultimately a failure for political and aesthetic reasons.